Pengaruh Motivasi Intrinsik pada Kepuasan Kerja dan Dampaknya pada Organizational Citizenship Behavior - Ignatius Soni; Tri Ratna Purnamarini (Journal Of Business, Finance, and Economics (JBFE), 2023)
This study aims to analyze the effect of intrinsic motivation on organizational citizenship behavior (OCB), with job satisfaction as a mediating variable. The study used a population of all employees of PT Adi Satria Abadi Yogyakarta. Primary data was taken from 80 employees by accidental sampling. The data were analyzed using multiple linear regression analysis and the Sobel test. The results of the study stated that intrinsic motivation had a significant positive effect on job satisfaction, that intrinsic motivation had no significant effect on OCB, and that job satisfaction had no significant effect on OCB. The effect of intrinsic motivation on OCB is not mediated by job satisfaction variables